2008
DOI: 10.1111/j.1469-1795.2008.00170.x
|View full text |Cite
|
Sign up to set email alerts
|

The sleeping policeman: understanding issues of enforcement and compliance in conservation

Abstract: Rules governing human behaviour are at the heart of every system of natural resource management. Without compliance, however, rules are meaningless so effective enforcement is essential if conservation is to be successful. There is a large body of theory concerning enforcement and compliance with rules spread over several disciplines, including psychology, economics and sociology. However, there have been few attempts to extend this theory to conservation applications and there is little practical guidance for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
289
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 294 publications
(291 citation statements)
references
References 81 publications
1
289
0
1
Order By: Relevance
“…Efficient law enforcement is necessary for all natural resource management (Keane et al 2008). However, law enforcement measures often lead to the criticism that PAs are created by and for an elitist few, in conflict with local community interests (Wittemyer et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Efficient law enforcement is necessary for all natural resource management (Keane et al 2008). However, law enforcement measures often lead to the criticism that PAs are created by and for an elitist few, in conflict with local community interests (Wittemyer et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Declines in the numbers of large herbivores were attributed to cessation of anti-poaching activities during a period of economic decline. Analysis of the trends in the buffalo population over the whole area has suggested that population change was primarily due to illegal hunting, and that enforcement of wildlife laws reduced the illegal offtake (Hilborn et al 2006) a conclusion also reached for other areas (Hilborn et al 2006;Jachmann and Billiouw 1997;Keane et al 2008;Leader-Williams and Milner-Gulland 1993). Using 50 years of buffalo census data, Hilborn et al (2006) established that illegal hunting and enforcement activities could account for the overall trends in buffalo population yet examination of the buffalo total counts indicated variation in the buffalo population recovery; some areas have almost completely recovered from the population low of 1994 and other areas have failed to recover.…”
Section: Introductionmentioning
confidence: 99%
“…Models of enforcement and compliance have generally assumed that individuals are influenced by their perceptions of the risk of punishment and the potential rewards (Garoupa 1997;Keane et al 2008). Few of these models have incorporated heterogeneity in individual characteristics, but the aggregate effect of individual differences in behaviour may have important consequences for conservation outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Rules are ubiquitous in conservation and resource management, and essential for their success (Ostrom 1990;Gibson et al 2005;Keane et al 2008), yet the question of how best to design and enforce systems of rules governing local-level resource use has been particularly neglected in conservation research (Robinson et al 2010). To predict the effects of an enforcement regime, it is not only necessary to understand how an intervention affects the choices of potential rule breakers, but also how it influences the behaviour of those responsible for monitoring non-compliance, and how these decisions interact (Akella & Canon 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation